Administrative-Legal Aspects of Informatisation of the Health Care Sector in Poland. E-Health in the Era of COVID-19 Pandemic - Skoczylas, Dominika (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The aim of the article is to present basic legal solutions in the field of informatisation of the health care sector in Poland. The article mainly deals with administrative-legal aspects related to the use of information and communication technologies in the field of health care. It reviews and assesses the legal regulations emerging in an extraordinary situation, such as the COVID-19 pandemic. The subject of consideration was the legal, social and technological issues of implementing new regulations during the pandemic. The analysis of the topic made it possible to answer the questions of whether interest in medical e-services has increased in the era of the COVID-19 pandemic and whether their provision has been effective and safe. According to the analysis, there is an increasing trend in the use of electronic means of communication in the health sector, hence its informatisation is a dynamic process. It was confirmed that medical services should be tailored to the needs of patients (personalisation of services) and secure, and therefore it is also necessary to strengthen cybersecurity measures for service provision in the health sector. Research methods include the analysis of basic legal acts with the use of the literature on the subject.